The mood of elite Polish athletes and p.e. students during the first wave of the COVID-19 pandemic - Guszkowska, M.; Szczypinska, M.; Samelko, A. (Studies in Sport Humanities, 2020)
The aim of the study was to compare mood during the fi rst wave of the COVID-19 pandemic in athletes - potential Olympians (n = 57, including 28 men and 29 women) involved in Olympic preparations and extramural physical education students (n = 54, including 28 men and 26 women). The age of the subjects was between 18 and 45 years. The additional objective was to determine diff erentiation according to gender. The Polish version of the Profi le of Mood States by McNair, Lorr & Droppleman was used in the form of an on-line survey. There were no signifi cant differences between the men and women (main gender eff ect). The athletes demonstrated lower levels of anger and confusion than the students (main group eff ect). In the case of tension, a signifi cant interaction was found between the group and gender: among athletes, a lower level of tension was found in men, and among students - in women